Peran audit internal dan whistleblowing system dalam mendeteksi dan mencegah fraud laporan keuangan - Seftya Khairun Nisa; Widiar Onny Kurniawan; Sabrina Ricke Fadilla (Nur Science Institute, 2025)
Fraud in financial reports is a serious problem that can harm companies and stakeholders. The impact is not only felt on the economic aspect, but also damages reputation and public trust. Therefore, it is essential to have an effective system in place to detect and prevent fraud, with internal audit and whistleblowing systems as key elements. This research uses a literature review approach to collect data from relevant journals and sources to explore the roles of internal audit and whistleblowing systems in detecting and preventing fraud. The research results show that an effective internal audit can identify risks and weaknesses in internal control, thereby reducing the likelihood of fraud. In addition, companies that implement effective whistleblowing systems provide employees with channels to report fraud, thereby facilitating early detection. This finding confirms that integrating the two systems can significantly reduce fraud. As the information presented in the financial reports is reliable and in accordance with accounting principles, there is no evidence of deliberate manipulation. In conclusion, the effective implementation of internal audit and whistleblowing systems can increase transparency, accountability, and integrity of financial reports.